Pengaruh Perputaran Kas terhadap Profitabilitas Perusahaan Sub Sektor Makanan dan Minuman - Gianti Ajeng Cahyani; Andri Indrawan; Tina Kartini (BUDGETING : Journal of Business, Management and Accounting, 2020)
This study aims to determine the effect of cash turnover on the profitability of food and beverage sub-sector companies listed on the IDX. The study was conducted using quantitative methods using an associative approach. Samples were taken by purposive sampling technique. The data collected is secondary data with classical assumption test analysis techniques, multiple linear regression analysis, and hypothesis testing. The results showed that cash turnover partially had a negative effect on profitability with t test results of -2.666 with a significant value of 0.012. T-value of -2.666 <ttable 2.034, can be interpreted that Ha is accepted and Ho is rejected, meaning that cash turnover affects the company's ROA and a significant value of 0.012 <0.05, indicating a significant effect. Conclusion, cash turnover has a negative effect because the size of the profitability (ROA) is not influenced by cash turnover. Sometimes when cash turnover increases, the profitability of the company is actually smaller than the previous year, because profitability is not only influenced by cash turnover, but can also be influenced by the accounts receivable turnover and inventory turnover Keywords: Cash Turnover and Profitability